ADSORPSI ASAM LEMAK BEBAS DALAM MINYAK SAWIT MENTAH MENGGUNAKAN ADSORBEN ABU TANDAN KOSONG SAWIT - M Syahwandi; Winda Rahmalia; Titin Anita Zahara; Thamrin Usman (Tanjungpura University, 2019)
Research on the use of the oil palm empty fruit bunch (OPEFB) as an adsorbent for free fatty acid (FFA) adsorption on Crude Palm Oil (CPO) has been done. CPO is the main raw material in the manufacture of food products. The results of OPEFB adsorbent characteristics showed the amount of water content and ash content of 0,067% and 0,175%, XRF analysis obtained the greatest content of OPEFB in the form potassium metal as much as 44,24%, FTIR analysis identified that there were CO3 compounds in wave number 1648 cm-1 and SEM analysis indicates there are no pores in OPEFB. The result showed that the number of OPEFB with the best adsorption was 0,1 gram with 60 minute optimum contact time. The CPO adsorption process with OPEFB shows the Langmuir model with a correlation value (R2) of 0,8845 and the adsorptions kinetics follows the pseudo order 2 adsorption kinetics model with a correlation value (R2) of 0,9857. The results of this study showed the characteristics of CPO before and after adsorbed using 0,1 g of adsorbent OPEFB showed the amount of FFA level of 7,321% to 6,297%, water content of 0,0025% to 0,00119% and impurities content of 0,8847% to 0,8408%.